Bone filling material and preparation method and application thereof

By introducing flexible silicone segments into bone cement materials and reducing their flexural modulus, the osteoporosis and refraction problems caused by excessive flexural strength of existing bone cement materials are solved, and the mechanical properties closer to natural bone tissue and lower stress shielding effect are achieved.

CN118892576BActive Publication Date: 2025-03-11TIANJIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411397910.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-03-11
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The bending strength of existing bone cement materials is too high, resulting in stress shielding of bone structures, causing the risk of osteoporosis and refraction, especially after vertebroplasty.

Method used

By introducing flexible siloxane segments into acrylate polymers, the bending modulus of the bone filler material is reduced, making its mechanical properties closer to natural bone tissue.

Benefits of technology

It reduces the stress shielding effect after vertebroplasty, reduces the incidence of adjacent vertebral fractures, and improves the developer affinity of the material, reducing the risk of developer particles falling off and embolization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118892576B_ABST
    Figure CN118892576B_ABST
Patent Text Reader

Abstract

The present invention provides a bone filling material and a preparation method and application thereof, belonging to the technical field of medical materials for repairing bone defects. The bone filling material includes a powder and a liquid, and the amount of the powder added in the unit volume of the liquid is 1.5-2.5g; wherein, by mass percentage, the powder includes: a composite material 10-89.99%, a first acrylic polymer 0-59.5%, a developer 10-50%, and benzoyl peroxide 0.01-3%; by mass percentage, the liquid includes: a first acrylic monomer 94.5-99.98%, N, N-dimethyl-p-toluidine 0.01-5%, and an inhibitor 0.01-0.5%; the above-mentioned composite is a copolymer or blend formed by a second acrylic polymer and a siloxane compound, or a copolymer or blend formed by a second acrylic polymer, a siloxane compound and methacrylate silane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical materials for repairing bone defects, and in particular relates to a bone filling material and a preparation method and application thereof. Background Art

[0002] Bone cement is used as an alternative material for artificial bone, shoulder, arm, leg and other bone repair, and can also be used for bone defect repair in maxillofacial surgery and dental surgery. It includes acrylic resin bone cement, calcium salt bone filling implants, allogeneic bone repair materials, metal fillers, etc.

[0003] Acrylic resin (PMMA) bone cement is a biomaterial with self-setting properties used to fill the gap between bone and implant or bone cavity. It is becoming more and more popular in minimally invasive surgery. PMMA bone cement has good injection performance, can be arbitrarily shaped, and can be developed under X-ray after adding developer. Advantages such as that have established its dominant position in orthopedic surgery. However, the current commercial spinal bone cement has a bending strength of up to 50-70MPa, while the bending strength of the spine itself is only about 20MPa. Excessive bending strength can cause stress shielding effect of bone structure. When stress shielding occurs in bone tissue, the stress on the vertebral body is at a low level for a long time, causing bone tissue to gradually resorb, resulting in further osteoporosis at the fracture site, which becomes an important cause of re-fracture after vertebroplasty. According to follow-up after vertebroplasty, the incidence of vertebral re-fracture in non-surgical sites after 1 year is as high as 21.82%. Therefore, the development of bone repair materials with lower bending modulus matching the vertebral body is of great significance for the treatment of geriatric bone diseases and the expansion of bone repair applications. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a bone filling material and a preparation method and application thereof, in order to at least partially solve the above technical problems. The specific technical solutions provided by the present invention are as follows.

[0005] As a first aspect of the present invention, a bone filling material is provided, comprising powder and liquid, wherein the amount of powder added to a unit volume of liquid is 1.5-2.5 g;

[0006] Wherein, in terms of mass percentage, the above powder includes:

[0007] Complex 10-89.99%,

[0008] The first acrylic polymer 0-59.5%,

[0009] Developer 10-50%,

[0010] Benzoyl peroxide 0.01-3%;

[0011] In terms of mass percentage, the above liquids include:

[0012] The first acrylic acid ester monomer is 94.5-99.98%,

[0013] N, N-dimethyl-p-toluidine 0.01-5%,

[0014] Inhibitor 0.01-0.5%;

[0015] The composite is a copolymer or blend formed by the second acrylic polymer and the siloxane compound, or a copolymer or blend formed by the second acrylic polymer, the siloxane compound and methacrylate silane.

[0016] As a second aspect of the present invention, a method for preparing the above-mentioned bone filling material is provided, comprising:

[0017] The composite, the first acrylic polymer, the developer, and benzoyl peroxide are mixed to obtain a powder of the bone filling material;

[0018] Mixing the first acrylic ester monomer, N,N-dimethyl-p-toluidine, and a polymerization inhibitor to obtain a liquid bone filling material;

[0019] adding the powder into the liquid and mixing to obtain a bone filling material;

[0020] Among them, the amount of powder added per unit volume of liquid is 1.5-2.5g;

[0021] The composite is a copolymer or blend formed by the second acrylic polymer and the siloxane compound, or a copolymer or blend formed by the second acrylic polymer, the siloxane compound and methacrylate silane.

[0022] As a third aspect of the present invention, there is provided an application of the above-mentioned bone filling material, comprising at least one of the following:

[0023] Application in the treatment of osteoporotic fractures;

[0024] Application in the treatment of maxillofacial bone defect repair materials;

[0025] Application in the treatment of dental bone defect repair materials;

[0026] Application in plastic surgery filling materials;

[0027] Application in the treatment of infectious arthritis materials;

[0028] Application in the treatment of bone defect filling materials.

[0029] Based on the above technical solution, a bone filling material and a preparation method and application thereof provided by the present invention have at least one of the following beneficial effects.

[0030] (1) In the embodiments of the present invention, siloxane compounds are used as flexible materials with high biosafety in the medical field to prepare medical devices, artificial joints, etc., but their high flexibility and polymerization rate make them unsuitable for use in bone filling materials that need to bear weight. Acrylic bone filling materials have a stiffness and strength far exceeding that of the vertebral body. After use, they are prone to cause stress shielding effect of the bone structure, resulting in further osteoporosis at the fracture site. Therefore, the present invention proposes a new bone filling material comprising a second acrylic polymer, a siloxane compound or a composite formed by a second acrylic polymer, a siloxane compound and methacrylate silane, and a liquid, wherein a flexible siloxane segment is introduced into the second acrylic polymer to reduce the stiffness and strength of the acrylic bone filling material, thereby obtaining a bone filling material with a lower bending modulus. This lower modulus bone filling material helps to reduce the stress shielding effect after vertebroplasty and reduce the incidence of adjacent vertebral fractures.

[0031] (2) In the embodiment of the present invention, the powder raw material and the liquid raw material only need to be mixed and packaged, and then the powder and liquid are mixed evenly in proportion when used in surgery to obtain the bone filling material. The preparation method is simple, takes a short time, and has no requirements for temperature and equipment. It is suitable for surgical operations or other commercial applications. In addition, the prepared bone filling material has a longer operation time and better injection performance. It is smoother and more convenient to use during surgery, which is conducive to the development of minimally invasive surgery.

[0032] (3) In the embodiments of the present invention, by introducing flexible siloxane segments, the bone filling material has lower compressive strength and bending modulus. By adjusting the amount of siloxane compounds added, the mechanical properties of the bone filling material are closer to those of natural bone tissue, which can reduce the stress shielding phenomenon after implantation. At the same time, the modified bone filling material has a higher affinity with the developer, which can reduce the shedding of the developer particles, thereby reducing the probability of embolism caused by the developer particles entering the blood, which has unexpected effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The graphs show the in vitro cytotoxicity test results of bone filling materials in different embodiments and comparative examples of the present invention. DETAILED DESCRIPTION

[0034] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings.

[0035] An ideal bone filling material should not only be able to restore and maintain the biomechanical stability of the fractured vertebra for a long time, but should also be non-toxic, have appropriate viscosity, solidify quickly and generate less heat, have adjustable strength and modulus, have biocompatibility, biodegradability, osteoconductivity and osteogenic activity, have mechanical properties close to those of natural bone tissue, and be suitable for commercial promotion.

[0036] Existing acrylic bone filling materials (bone cement) have much higher stiffness and strength than the vertebral body, which may lead to non-surgical vertebral fractures in patients after vertebroplasty. Therefore, a bone filling material that matches the strength of the patient's vertebral body is urgently needed. Siloxane compounds are a kind of flexible polymer material with lower stiffness and strength. Siloxane compounds have higher bond energy (445KJ / mol) and multiple methyl groups (CH 3 ) groups, which makes it resistant to the effects of extreme temperature, aging, oxidation, moisture and ultraviolet radiation. At the same time, siloxane compounds are also a non-irritating polymer material that can be used in the human body. Siloxane compounds have excellent biocompatibility and are not easy to cause foreign body reactions in the body. They can be used to prepare medical devices, artificial joints and implants, etc. They can be compounded with other materials to change the material properties, and can also be used to prepare drug controlled release systems and biosensors. In addition to the above-mentioned applications in the medical field, siloxane compounds also have a variety of applications in the fields of coatings, preservatives, building materials, textiles, etc., and their unique physical and chemical properties make them indispensable materials. However, due to the high flexibility and low polymerization rate of siloxane compounds, they are not suitable for use in bone filling materials that need to bear weight. Therefore, the present invention provides a bone filling material and a preparation method and application thereof. The present invention uses a high-flexibility siloxane compound to copolymerize and / or blend with a second acrylic ester polymer, and blends with a first acrylic ester polymer, benzoyl peroxide and a developer to obtain a powder of a bone filling material with a lower modulus, and finally mixes with a liquid of the bone filling material in proportion to obtain a bone filling material. By introducing a flexible siloxane segment polymer into the second acrylic polymer, the compressive strength and bending modulus of the second acrylic polymer (acrylic resin bone cement) are reduced, so that the mechanical properties of the obtained bone filling material are closer to the natural bone tissue of the human body.

[0037] Specifically, as a first aspect of the present invention, a bone filling material is provided, comprising powder and liquid, wherein the amount of powder added to a unit volume of liquid is 1.5-2.5 g;

[0038] Wherein, in terms of mass percentage, the above powder includes:

[0039] Complex 10-89.99%,

[0040] The first acrylic polymer 0-59.5%,

[0041] Developer 10-50%,

[0042] Benzoyl peroxide 0.01-3%;

[0043] In terms of mass percentage, the above liquids include:

[0044] The first acrylic acid ester monomer is 94.5-99.98%,

[0045] N, N-dimethyl-p-toluidine 0.01-5%,

[0046] Inhibitor 0.01-0.5%;

[0047] The composite is a copolymer or blend formed by the second acrylic polymer and the siloxane compound, or a copolymer or blend formed by the second acrylic polymer, the siloxane compound and methacrylate silane.

[0048] In the embodiments of the present invention, siloxane compounds are used as a flexible material with high biosafety in the medical field to prepare medical devices, artificial joints, etc., but their high flexibility and polymerization rate make them inapplicable to bone filling materials that need to bear weight. Acrylic bone filling materials have a stiffness and strength far exceeding that of the vertebral body, and are prone to cause stress shielding effect of the bone structure after use, resulting in further osteoporosis at the fracture site. Therefore, the present invention proposes a novel bone filling material comprising a second acrylic polymer, a siloxane compound or a composite formed by a second acrylic polymer, a siloxane compound and methacrylate silane, and a liquid, wherein a flexible siloxane segment is introduced into the second acrylic polymer to reduce the stiffness and strength of the acrylic bone filling material, thereby obtaining a bone filling material with a lower bending modulus. This lower modulus bone filling material helps to reduce the stress shielding effect after vertebroplasty and reduce the incidence of adjacent vertebral fractures.

[0049] According to an embodiment of the present invention, the composite formed by the second acrylic polymer, the siloxane compound or the second acrylic polymer, the siloxane compound and the methacrylate silane in the embodiment of the present invention is obtained by the following method: dissolving the second acrylic polymer in the siloxane compound, or dissolving the second acrylic polymer in the siloxane compound and the methacrylate silane, adding benzoyl peroxide and N, N-dimethyl-p-toluidine, stirring at 37°C for 2h and filtering the precipitate to obtain the composite. Wherein, when the composite does not contain methacrylate silane, the mass ratio of the second acrylic polymer and the siloxane compound is 1-2:1; when the composite contains methacrylate silane, the ratio of the second acrylic polymer, the siloxane compound and the methacrylate silane is 2-4:1:1. By adjusting the ratio of the second acrylic polymer, the siloxane compound and the methacrylate silane, the obtained composite can achieve the expected rigidity and strength. When the composite contains methacrylate silane, the methacrylate silane is used to bridge the acrylic polymer and the siloxane compound, so the amounts of methacrylate silane and the siloxane compound are kept consistent.

[0050] According to an embodiment of the present invention, the siloxane compound is 1,3-divinyltetramethyldisiloxane. The siloxane compound contains a silicon-oxygen bond, which makes it highly flexible. The second acrylic polymer is modified by the siloxane compound so that the modified second acrylic polymer has a certain flexibility, thereby reducing the rigidity and strength of the bone filling material finally prepared.

[0051] According to an embodiment of the present invention, the methacrylate silane includes one or more of 3-(trimethoxysilyl)propyl methacrylate, γ-methacryloxypropyl triethoxysilane, and methacryloxypropyl trimethoxysilane. This compound containing both an acrylate group and a silicon-oxygen bond can act as a bridge between the second acrylate polymer and the siloxane compound, wherein the acrylate group can form a strong chemical bond or interaction with the second acrylate polymer, while the silicon-oxygen bond can be compatible with and interact with the siloxane compound. Through dual affinity, the methacrylate silane realizes the combination of the second acrylate polymer and the siloxane compound, thereby improving the overall performance and stability of the composite. In addition to the methacrylate silane mentioned above, other compounds containing both an acrylate group and a silicon-oxygen bond can also be used.

[0052] According to an embodiment of the present invention, the first acrylic polymer and the second acrylic polymer include independently selected polymethyl methacrylate, or a copolymer formed by methyl methacrylate and one or more of the second acrylic monomers and / or styrene, wherein polymethyl methacrylate is a homopolymer of methyl methacrylate; the second acrylic monomer includes one or more of methyl methacrylate, ethyl methacrylate, butyl methacrylate, hydroxyethyl methacrylate, methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, isooctyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, hexyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate. By copolymerizing methyl methacrylate with one or more of the second acrylic ester monomer and / or styrene, other groups are introduced compared to polymethyl methacrylate, and the added amount of the second acrylic ester monomer and / or styrene is adjusted to make the strength and stiffness of the acrylic ester polymer adjustable. At the same time, more excellent properties such as toughness, processing performance, weather resistance, etc. can be given to it while maintaining stiffness and strength.

[0053] According to an embodiment of the present invention, the first acrylic acid ester monomer is selected from one or more of methyl methacrylate, ethyl methacrylate, butyl methacrylate, hydroxyethyl methacrylate, methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, isooctyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, hexyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate. In addition to the acrylic acid ester monomers mentioned above, other acrylic acid ester monomers not mentioned may also be used.

[0054] According to an embodiment of the present invention, the developer includes one or more of barium sulfate, zirconium dioxide, iopamidol, iohexol, sodium diatrizoate, and metal tantalum. Adding a developer can enhance the visibility of bone filling materials in medical images (such as X-rays, CT, etc.). By adding a developer, the distribution of bone filling materials, whether they are evenly filled, and whether there are leakage problems can be observed more accurately, thereby ensuring the effect of the operation. After the operation, medical images can be used to evaluate the curing of the bone filling material, the degree of integration with surrounding tissues, and whether there are complications.

[0055] According to an embodiment of the present invention, the polymerization inhibitor includes one or more of hydroquinone, p-benzoquinone, and 1,1-diphenyl-2-trinitrophenylhydrazine. The main function of adding the polymerization inhibitor to the bone filling material is to prevent the first acrylate monomer from polymerizing prematurely during the mixing and curing process, to ensure that the bone filling material maintains plasticity and fluidity during use, and to facilitate surgical operations. At the same time, the polymerization inhibitor can also control the curing time, reduce the heat release during the curing process, reduce the risk of thermal damage to surrounding tissues, and ensure the safety of the operation.

[0056] According to an embodiment of the present invention, the powder further includes one or more of auxiliary materials and pigments. The auxiliary materials include one or more of osteoporosis treatment drugs, antibiotics, hydroxyapatite, tricalcium phosphate, calcium sulfate, dicalcium silicate, tricalcium silicate, and bioglass. Osteoporosis treatment drugs include one or more of bisphosphonates, denosumab, romozumab, parathyroid hormone, and vitamins, wherein bisphosphonates include alendronate, neridronate, and ibandronate, and vitamins include vitamin D and vitamin K. Antibiotics play a role in preventing inflammation. Hydroxyapatite (HA), tricalcium phosphate (TCP), calcium sulfate, dicalcium silicate, and tricalcium silicate can enhance the biocompatibility of bone filling materials. Bioglass can be used to enhance the mechanical properties of bone filling materials. Pigments include one or more of chlorophyll pigments and carotene pigments. Pigments are added to bone filling materials so that there is a significant contrast effect during surgery, which helps doctors clearly identify the location and distribution of bone filling materials in the surgical area, especially in micro-invasive surgery or repair surgery, which facilitates the removal of excess bone filling materials or delicate operations. In addition to the above-mentioned chlorophyll pigments and carotene pigments, other colored pigments can also be used, such as phycocyanin, gardenia yellow and other edible pigments.

[0057] As a second aspect of the present invention, a method for preparing the above-mentioned bone filling material is provided, comprising:

[0058] The composite, the first acrylic polymer, the developer, and benzoyl peroxide are mixed to obtain a powder of the bone filling material;

[0059] Mixing the first acrylic ester monomer, N,N-dimethyl-p-toluidine, and a polymerization inhibitor to obtain a liquid bone filling material;

[0060] adding the powder into the liquid and mixing to obtain a bone filling material;

[0061] Among them, the amount of powder added per unit volume of liquid is 1.5-2.5g;

[0062] The composite is a copolymer or blend formed by the second acrylic polymer and the siloxane compound, or a copolymer or blend formed by the second acrylic polymer, the siloxane compound and methacrylate silane.

[0063] In the embodiment of the present invention, the powder raw material and the liquid raw material only need to be mixed and packaged, and then the powder and liquid are mixed evenly in proportion when used in surgery to obtain the bone filling material. The preparation method is simple, takes a short time, and has no requirements for temperature and equipment, which is suitable for surgical operations or other commercial applications. In addition, the prepared bone filling material has a longer operation time and better injection performance, and is smoother and more convenient to use during surgery, which is conducive to the development of minimally invasive surgery.

[0064] According to an embodiment of the present invention, the mixing method in the preparation method of the above-mentioned bone filling material is not limited, and is limited to a state of uniform mixing. Specifically, according to the stirring time that can make the bone filling material reach a uniform mixing state under normal conditions, the preparation method provided below can be used for preparation:

[0065] Add the composite, the first acrylic polymer, the developer, and benzoyl peroxide into a three-dimensional mixer, and stir at a speed of 100-300 r / min for 2-3 hours until the mixture is uniform, to obtain a powder of the bone filling material;

[0066] Add the first acrylic ester monomer, N,N-dimethyl-p-toluidine, and the polymerization inhibitor into a mixing device, and stir at a speed of 100-300 r / min for 3-5 minutes until the mixture is uniform, to obtain a liquid of the bone filling material;

[0067] The powder obtained above is added to the liquid obtained above in proportion, and stirred for 30-60 seconds until it is uniform. During the stirring process, the powder and the liquid undergo a self-polymerization reaction, and the bone filling material is obtained after the self-polymerization reaction is completed.

[0068] As a third aspect of the present invention, there is provided an application of the above-mentioned bone filling material, comprising at least one of the following:

[0069] Application in the treatment of osteoporotic fractures;

[0070] Application in the treatment of maxillofacial bone defect repair materials;

[0071] Application in the treatment of dental bone defect repair materials;

[0072] Application in plastic surgery filling materials;

[0073] Application in the treatment of infectious arthritis materials;

[0074] Application in the treatment of bone defect filling materials.

[0075] In the embodiments of the present invention, by introducing flexible siloxane segments, the bone filling material has lower compressive strength and bending modulus, and by adjusting the amount of siloxane compounds added to make its mechanical properties closer to natural bone tissue, the stress shielding phenomenon after implantation can be reduced. At the same time, the modified bone filling material has a higher affinity with the developer, which can reduce the shedding of developer particles, thereby reducing the probability of embolism caused by developer particles entering the blood, which has unexpected effects.

[0076] According to an embodiment of the present invention, the above-mentioned bone filling material can be used for filling vertebral bodies in vertebroplasty and kyphoplasty; it is also suitable for fixation of metal or polymer implants to living bones in arthroplasty, spinal or trauma surgery; or it can be used together with internal fixation products for the treatment of osteoporotic fractures occurring in the upper limbs, lower limbs or pelvis.

[0077] According to an embodiment of the present invention, the above-mentioned bone filling material is suitable for bone defect repair in maxillofacial surgery and dental surgery, including: expansion or reconstruction of the alveolar ridge, filling of extraction sockets; dental implant surgery: preparation of implant bed, bone defect filling, maxillary sinus lift; periodontal treatment: bone defect filling, guided tissue regeneration (GTR) and guided bone regeneration (GBR).

[0078] According to an embodiment of the present invention, the above-mentioned bone filling material is suitable for surgical plastic surgery, such as craniomaxillofacial plastic surgery, skull repair plastic surgery, back of the head flattening plastic surgery, top of the head filling plastic surgery, nasal bone plastic surgery and other bone shaping and filling.

[0079] The present invention is further described below by examples and related test experiments. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention. However, it is obvious that one or more embodiments may also be implemented without these specific details. And, in the absence of conflict, the details in the following embodiments may be combined into other feasible embodiments at will. All instruments, consumables and reagents in the following examples, if not otherwise specified, may be obtained from commercial sources.

[0080] Example 1

[0081] The bone filling material in this embodiment 1 includes powder and liquid, wherein the amount of powder added to the unit volume of liquid is 2.5 g.

[0082] The powder includes the following raw materials in percentage by weight: 79.99wt% of the composite, 10wt% of polymethyl methacrylate, 10wt% of barium sulfate, and 0.01wt% of benzoyl peroxide.

[0083] The liquid includes the following raw materials in percentage by mass: 99.98 wt % of methyl methacrylate, 0.01 wt % of N,N-dimethyl-p-toluidine, and 0.01 wt % of hydroquinone.

[0084] The bone filling material in this Example 1 is prepared according to the following steps.

[0085] Polymethyl methacrylate was dissolved in 3-(trimethoxysilyl)propyl methacrylate (TMSPMA) and 1,3-divinyltetramethyldisiloxane, benzoyl peroxide and N,N-dimethyl-p-toluidine were added, and the mixture was stirred at 37°C for 2 hours, and then the precipitate was filtered to obtain a composite. Among them, the mass percentage of polymethyl methacrylate was 49.99wt%, the mass percentage of 3-(trimethoxysilyl)propyl methacrylate was 24.995wt%, the mass percentage of 1,3-divinyltetramethyldisiloxane was 24.995wt%, the mass percentage of benzoyl peroxide was 0.01wt%, and the mass percentage of N,N-dimethyl-p-toluidine was 0.01wt%.

[0086] The composite, polymethyl methacrylate, barium sulfate and benzoyl peroxide were added into a mixer and stirred at a speed of 200 r / min for 4 minutes until the mixture was uniform, thereby obtaining a bone filling material powder.

[0087] Methyl methacrylate, N,N-dimethyl-p-toluidine and hydroquinone were added into a mixing device, and stirred at a speed of 200 r / min for 4 minutes until the mixture was uniform, thereby obtaining a bone filling material liquid.

[0088] The bone filling material powder obtained above is added into the bone filling material liquid obtained above according to a certain proportion, and stirred for 45 seconds until it is in a uniform state, thereby obtaining the bone filling material.

[0089] Example 2

[0090] The bone filling material in this embodiment 2 includes powder and liquid, wherein the amount of powder added to the unit volume of liquid is 2 g.

[0091] The powder includes the following raw materials in percentage by weight: 40 wt % of the composite, 29.5 wt % of polymethyl methacrylate, 30 wt % of barium sulfate, and 0.5 wt % of benzoyl peroxide.

[0092] The liquid includes the following raw materials in percentage by weight: 94.5 wt % of methyl methacrylate, 5 wt % of N,N-dimethyl-p-toluidine, and 0.5 wt % of hydroquinone.

[0093] The preparation method of the bone filling material in this embodiment 2 is the same as that in embodiment 1.

[0094] Example 3

[0095] The bone filling material in this embodiment 3 includes powder and liquid, wherein the amount of powder added to the unit volume of liquid is 1.5 g.

[0096] The powder includes the following raw materials in percentage by weight: 10 wt % of a composite, 59.5 wt % of polymethyl methacrylate, 30 wt % of barium sulfate, and 0.5 wt % of benzoyl peroxide.

[0097] The liquid includes the following raw materials in percentage by weight: 94.5 wt % of methyl methacrylate, 5 wt % of N,N-dimethyl-p-toluidine, and 0.5 wt % of hydroquinone.

[0098] The preparation method of the bone filling material in this embodiment 3 is the same as that in embodiment 1.

[0099] Comparative Example 1

[0100] In this comparative example 1, the bone filling material includes powder and liquid, wherein the amount of powder added to the unit volume of liquid is 2 g.

[0101] The powder includes the following raw materials in percentage by weight: 89.99 wt % of polymethyl methacrylate, 10 wt % of barium sulfate, and 0.01 wt % of benzoyl peroxide.

[0102] The liquid includes the following raw materials in percentage by weight: 94.5 wt % of methyl methacrylate, 5 wt % of N,N-dimethyl-p-toluidine, and 0.5 wt % of hydroquinone.

[0103] The preparation method of the bone filling material in Comparative Example 1 is the same as that in Example 1.

[0104] Testing and Characterization

[0105] The samples obtained from the above embodiments and comparative examples were subjected to relevant tests and characterizations.

[0106] In order to test the safety, effectiveness and stability of bone filling materials in clinical applications, the following tests were conducted. Specifically: under the conditions of (23±1)°C and relative humidity not less than 40%, the powder and liquid of the bone filling materials in the above embodiments and comparative examples were mixed in proportion, stirred for 1-2 minutes, left to stand and contacted the bone filling materials with fingers wearing dry surgical latex gloves every 10 seconds, and the temperature was recorded every 5 seconds with an infrared thermal imager. The time from the start of stirring when the powder of the bone filling material and the liquid are mixed to the time when the fingers wearing dry surgical latex gloves can be clearly separated when they first touch the surface of the bone cement is defined as the dough time of the bone filling material. The time from the start of mixing the powder of the bone filling material and the liquid to the time required for the bone filling material to be transformed into a solid solid is defined as the setting time of the bone filling material. Table 1 shows the safety, effectiveness and stability test results of Examples 1-3 of the present invention and Comparative Example 1.

[0107] Table 1 Safety, effectiveness and stability test results of Examples 1-3 and Comparative Example 1

[0108]

[0109] As can be seen from Table 1, the solidification time was extended from 13 minutes in Comparative Example 1 to a maximum of 28 minutes, reducing the drastic temperature rise caused by the rapid solidification of the bone filling material. The dough time was reduced from 60 seconds in Comparative Example 1 to a minimum of 20 seconds, which can make the surgical process faster and reduce the pain of the patient. The maximum temperature is less than 70°C, which can avoid the necrosis of the tissue in the surgical site of the patient due to overheating due to the large amount of heat released during the solidification process of the bone filling material, thereby reducing the harm to the patient.

[0110] Furthermore, in order to detect the mechanical properties of the bone filling material, the following test was conducted. Specifically, at (23±1)°C and a relative humidity of not less than 40%, the powder and liquid of the bone filling material in the above embodiment and comparative example were mixed in proportion, stirred for 1-2 minutes, and then poured into a fixed mold with a height of 12 mm and a diameter of 6 mm to conduct a mechanical property test of compressive strength.

[0111] At (23±1)°C and relative humidity not less than 40%, the powder and liquid of the bone filling material in the above embodiment and comparative example were mixed in proportion, stirred for 1-2 minutes, and then poured into a fixed mold with a length of 75 mm, a width of 10 mm, and a thickness of 3.3 mm to perform mechanical property tests on flexural strength and flexural modulus.

[0112] According to the method described in ISO 5833:2002 "Surgical Implants - Acrylic Resin Bone Cement", the mechanical properties of the bone filling materials of the above embodiments and comparative examples were tested. At the same time, in order to compare with the currently commonly used bone cements (Palacos® R, Refobacin-Palacos® G, CMW® 1, Sulfix® 6, Simplex® P), the present invention purchased commonly used bone cements and tested them in the above manner, and the results are shown in Table 2.

[0113] Table 2 Mechanical properties test results of Examples 1-3, Comparative Example 1 and commercially available bone cement

[0114]

[0115] It can be seen from Table 2 that the compressive strength, flexural strength and flexural modulus of the bone filling material provided by the present invention are much lower than those of Comparative Example 1 and commercially available bone cement, and the flexural strength is higher than the average strength of human vertebrae by 20 MPa. The mechanical properties are closer to natural bone tissue, which can reduce the stress shielding phenomenon after implantation and reduce the incidence of adjacent vertebral fractures after surgery.

[0116] Furthermore, in order to detect whether the bone filling material will cause toxic reactions in cells after being applied to the human body and contacting cells, the following tests were conducted.

[0117] The bone filling material was solidified into a 3mm thick and 6mm diameter disc for in vitro cytotoxicity test. The specific test content was: osteoblasts were cultured using DMEM culture medium (89% basic DMEM culture medium, 10% fetal bovine serum (FBS), 1% double antibody (a mixture of penicillin and streptomycin)), where the ratio of the solidified bone filling material mass to the culture medium volume was 1g:5mL to prepare the leaching solution. The cell density was adjusted to 10 5 200 μL per well was inoculated into a 96-well plate. Incubate at 37°C and 5% CO 2 After 24 hours of incubation in the incubator, the culture medium was removed and replaced with the extract. Only fresh culture medium was added to the negative control group. After 1 and 3 days of incubation, the culture medium and extract were removed from the wells, and then 180 μL of culture medium and 20 μL of thiazolyl blue (MTT, 1 mg / mL) were added to each well. Incubate at 37°C and 5% CO 2 After 4 hours of incubation in the incubator, the MTT was removed by aspiration, and an equal amount of dimethyl sulfoxide (DMSO) was added and shaken for 15 minutes. The optical density (OD value) of each well was measured on a microplate reader at a wavelength of 490 nm, and the relative cell proliferation rate (RGR) was calculated. There were 6 parallel samples. The formula for calculating RGR is shown in formula (1):

[0118] RGR = (OD value of experimental group / OD value of negative control group) × 100% (1)

[0119] Generally speaking, an RGR of more than 80% is considered to indicate that the bone filling material has good compatibility with cells, and if it is above 100%, it means that the bone filling material is conducive to cell proliferation.

[0120] Figure 1 The graphs show the in vitro cytotoxicity test results of bone filling materials in different embodiments and comparative examples of the present invention.

[0121] from Figure 1 It can be seen that after the osteoblasts were cultured in the bone filling material extracts of different groups for 1-3 days, the cell survival rate was above 80%, which proves that the bone filling material in the embodiment of the present invention has low cytotoxicity and good compatibility.

[0122] In summary, the present invention provides a bone filling material and a preparation method and application thereof, wherein the bone filling material provided by the present invention uses siloxane compounds and acrylic polymers to prepare a composite containing silicon oxygen bonds and acrylic groups, thereby reducing the bending modulus of acrylic polymers. The silicon oxygen bonds introduced at the same time are flexible covalent bonds. After addition, the flexibility of the bone filling material is enhanced, the rigidity is reduced, and the overall mechanical properties are more matched with natural bone tissue. It has the characteristics of biocompatibility, bending strength and bending modulus close to those of vertebral bodies, and low heat generation. It is simple to make and can play a supporting role in place of natural bone tissue. It is an excellent bone filling material suitable for the treatment of osteoporotic fractures, bone defect repair in maxillofacial surgery and dental surgery, and surgical plastic filling.

[0123] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A bone filling material, characterized in that: The bone filling material is suitable for vertebral bodies, and the bone filling material comprises powder and liquid, and the amount of the powder added to the unit volume of the liquid is 1.5-2.5 g; Wherein, in terms of mass percentage, the powder comprises: Complex 10-89.99%, The first acrylic polymer 0-59.5%, Developer 10-50%, Benzoyl peroxide 0.01-3%; In terms of mass percentage, the above liquids include: The first acrylic acid ester monomer is 94.5-99.98%, N, N-dimethyl-p-toluidine 0.01-5%, Inhibitor 0.01-0.5%; The composite is a copolymer or blend formed by a second acrylic polymer and a siloxane compound, or a copolymer or blend formed by a second acrylic polymer, a siloxane compound and methacrylate silane; The siloxane compound is 1,3-divinyltetramethyldisiloxane; When the composite is prepared without the methacrylate silane, the mass ratio of the second acrylic polymer to the siloxane compound is 1-2:1; When the composite is prepared to contain the methacrylate silane, the mass ratio of the second acrylic polymer, the siloxane compound and the methacrylate silane is 2-4:1:

1.

2. The bone filling material according to claim 1, characterized in that: The methacrylate silane includes one or more of 3-(trimethoxysilyl)propyl methacrylate, γ-methacryloxypropyl triethoxysilane, and methacryloxypropyl trimethoxysilane.

3. The bone filling material according to claim 1, characterized in that: The first acrylic polymer and the second acrylic polymer are independently selected from polymethyl methacrylate, or a copolymer formed by methyl methacrylate and one or more of the second acrylic monomer and / or styrene.

4. The bone filling material according to claim 1 or 3, characterized in that: The first acrylic ester monomer and the second acrylic ester monomer are each independently selected from one or more of methyl methacrylate, ethyl methacrylate, butyl methacrylate, hydroxyethyl methacrylate, methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, isooctyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, hexyl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate.

5. The bone filling material according to claim 1, characterized in that: The developer includes one or more of barium sulfate, zirconium dioxide, iopamidol, iohexol, sodium diatrizoate, and metal tantalum.

6. The bone filling material according to claim 1, characterized in that: The polymerization inhibitor includes one or more of hydroquinone, p-benzoquinone, and 1,1-diphenyl-2-trinitrophenylhydrazine.

7. The bone filling material according to claim 1, characterized in that: The powder also includes one or more of auxiliary materials and pigments; The auxiliary materials include one or more of osteoporosis treatment drugs, antibiotics, hydroxyapatite, tricalcium phosphate, calcium sulfate, dicalcium silicate, tricalcium silicate, and bioglass; The osteoporosis treatment drugs include one or more of bisphosphonates, denosumab, romosuzumab, parathyroid hormone, and vitamins; The pigment includes one or more of chlorophyll pigments and carotene pigments.

8. A method for preparing the bone filling material according to any one of claims 1 to 7, characterized in that: include: The composite, the first acrylic polymer, the developer, and benzoyl peroxide are mixed to obtain a powder of the bone filling material; Mixing the first acrylic ester monomer, N,N-dimethyl-p-toluidine, and a polymerization inhibitor to obtain a liquid bone filling material; adding the powder into the liquid and mixing them to obtain the bone filling material; Wherein, the amount of the powder added per unit volume of the liquid is 1.5-2.5 g; The composite is a copolymer or blend formed by a second acrylic polymer and a siloxane compound, or a copolymer or blend formed by a second acrylic polymer, a siloxane compound and methacrylate silane; The siloxane compound is 1,3-divinyltetramethyldisiloxane; When the composite is prepared without the methacrylate silane, the mass ratio of the second acrylic polymer to the siloxane compound is 1-2:1; When the composite is prepared to contain the methacrylate silane, the mass ratio of the second acrylic polymer, the siloxane compound and the methacrylate silane is 2-4:1:

1.

9. An application of the bone filling material according to any one of claims 1 to 7, characterized in that: The application includes at least one of the following: Application in the treatment of osteoporotic fractures; Application in the treatment of bone defect filling materials.

Citation Information

Patent Citations

  • Surface degraded injectable bone filling material and preparation method thereof

    CN107412850A

  • Curable composition with acrylic acid and silicone resin

    CN114521208A